Evaluation of brain lesion distribution criteria at disease onset in differentiating MS from NMOSD and MOG-IgG-associated encephalomyelitis. (April 2019) - Hyun, Jae-Won; Huh, So-Young; Shin, Hyun-June; Woodhall, Mark; Kim, Su-Hyun; Irani, Sarosh R; Lee, Sang Hyun; Waters, Patrick; Kim, Ho Jin
Objectives: We aimed to evaluate the utility of the recently described brain lesion distribution criteria to differentiate multiple sclerosis (MS) from aquaporin-4 immunoglobulin G-positive neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein immunoglobulin G-associated encephalomyelitis (MOG-EM) at disease onset in an Asian cohort. Methods: A total of 214 patients who fulfilled the published criteria for MS, NMOSD, or MOG-EM and underwent brain magnetic resonance imaging (MRI) within 3 months of disease onset were enrolled. The brain lesion distribution criteria were defined as the presence of a lesion adjacent to the body of the lateral ventricle and in the inferior temporal lobe, or an S-shaped U-fiber lesion, or a Dawson's finger-type lesion. Results: Brain lesions were identified in the initial MRI scans of 166/214 patients. The distribution criteria were applied to these scans (MS ( n = 94), NMOSD ( n = 64), and MOG-EM ( n = 8)). The sensitivity, specificity, and positive and negative predictive values of the criteria for MS versus NMOSD were 79.8%, 87.5%, 90.4%, and 74.7%, and for MS versus MOG-EM these were 79.8%, 100%, 100%, and 29.6%, respectively. Conclusion: These findings suggest that the brain lesion distribution criteria are helpful in distinguishing MS from NMOSD and MOG-EM in an Asian population, even at disease onset.